3+(-7)=f-3

Simple and best practice solution for 3+(-7)=f-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+(-7)=f-3 equation:


Simplifying
3 + (-7) = f + -3
3 + -7 = f + -3

Combine like terms: 3 + -7 = -4
-4 = f + -3

Reorder the terms:
-4 = -3 + f

Solving
-4 = -3 + f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-1f' to each side of the equation.
-4 + -1f = -3 + f + -1f

Combine like terms: f + -1f = 0
-4 + -1f = -3 + 0
-4 + -1f = -3

Add '4' to each side of the equation.
-4 + 4 + -1f = -3 + 4

Combine like terms: -4 + 4 = 0
0 + -1f = -3 + 4
-1f = -3 + 4

Combine like terms: -3 + 4 = 1
-1f = 1

Divide each side by '-1'.
f = -1

Simplifying
f = -1

See similar equations:

| 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 | | 10b+50=30 | | 10x^2+13x+-9=0 | | -(x+5)=-1 | | 5h-12=4h+6 | | 3(-4+3)=2 | | 8x^4-42x^2=0 | | 2(1[3u-7]1)=16 | | 2,5x-21=14 | | -4.6y=9.2 | | (8x^4-42x^2-10x)-3=0 | | 1-7(-2-8a)=-433 | | (-2)+(-3)+(-2)= | | 0,5x-3=15 | | -2x+1=-18 | | 3x-4(x-8)=34 | | (-5)+(-4)+(-2)= | | y=6x+33 | | 2x^3+9x^2+7x-24=0 | | 2(x-2)=-3x+36 | | -a-3+7=a |

Equations solver categories